2017
DOI: 10.1007/s00203-017-1422-x
|View full text |Cite
|
Sign up to set email alerts
|

Revealing strategies of quorum sensing in Azospirillum brasilense strains Ab-V5 and Ab-V6

Abstract: Azospirillum brasilense is an important plant-growth promoting bacterium (PGPB) that requires several critical steps for root colonization, including biofilm and exopolysaccharide (EPS) synthesis and cell motility. In several bacteria these mechanisms are mediated by quorum sensing (QS) systems that regulate the expression of specific genes mediated by the autoinducers N-acyl-homoserine lactones (AHLs). We investigated QS mechanisms in strains Ab-V5 and Ab-V6 of A. brasilense, which are broadly used in commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 56 publications
3
30
0
1
Order By: Relevance
“…In relation to the PGPB A. brasilense strains Ab‐V5 and Ab‐V6, we have shown that their genomes encompass 14 and 15 putative lux genes, respectively, representing eight different putative luxR ‐type transcriptional regulatory genes, duplicated throughout the genomes; no luxI gene was detected in any of the strains, confirming our previous report . This observation is in agreement with the reports that luxI genes are rare in Azospirillum , although they have been detected in A. lipoferum , but not in A. brasilense .…”
Section: Discussionsupporting
confidence: 91%
“…In relation to the PGPB A. brasilense strains Ab‐V5 and Ab‐V6, we have shown that their genomes encompass 14 and 15 putative lux genes, respectively, representing eight different putative luxR ‐type transcriptional regulatory genes, duplicated throughout the genomes; no luxI gene was detected in any of the strains, confirming our previous report . This observation is in agreement with the reports that luxI genes are rare in Azospirillum , although they have been detected in A. lipoferum , but not in A. brasilense .…”
Section: Discussionsupporting
confidence: 91%
“…Although the genomes of the two strains show high identity of nucleotides (unpublished genomes, but with average nucleotide identity of 99.99%), differences in the CDW and growth in different formulations point out to probable differences in their metabolism. Other mechanisms controlling cell growth, such as quorum sensing (Boyer and Wisniewski-Dyé, 2009), deserve to be investigated, and indeed, Fukami et al (2017a) have recently shown differences between Ab-V5 and Ab-V6 in quorum sensing mechanisms. Differences were also observed between the strains and formulations in the production of PHB, overall being higher in Ab-V6 and in FORM2+P3.…”
Section: Cell Dry Weight Accumulation and Accumulation Of Polyhydroxymentioning
confidence: 99%
“…Watnick and Kolter (2000) suggested that biofilm-forming microorganisms can return to mobile lifestyles when nutrient availability becomes scarce, a likely response to the search for new sources of nutrients; the change in lifestyle may result in the colonization of new environments (Costerton et al, 1995). However, intriguingly, biofilm formation in Ab-V5 was not affected by the medium composition and as biofilm is also related to quorum sensing (Boyer and Wisniewski-Dyé, 2009;Fukami et al, 2017a), this is an additional evidence pointing out that the differences between the two strains might be related to this mechanism.…”
Section: Synthesis Of Biofilmmentioning
confidence: 99%
See 2 more Smart Citations